2015
DOI: 10.1021/acs.cgd.5b00995
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Efficacy and Potency of Novel Small Molecule Ice Recrystallization Inhibitors

Abstract: The effects of ice recrystallization are well-recognized throughout the literature. This phenomenon is the major cause for cellular damage during thawing of cells, ultimately reducing post-thaw viability and function. In this paper, we describe a method for quantifying the inhibitory effect on ice recrystallization of novel small molecules that are cryoprotectants for red blood cells. The method is ideally suited to the splat-cooling assay, where high-ice volume fractions are present. Using our method, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Similarly, these are used to measure the effectiveness of IBP analogues. Quantitative assays and image analysis routines have been developed to accurately measure thermal hysteresis (TH) activity, 63 66 ice recrystallization inhibition (IRI) activity, 56 , 67 , 68 dynamic ice-shaping (DIS), 69 and ice nucleation (IN) activity. 70 Furthermore, ice-binding can be detected directly, albeit in a qualitative fashion, by ice-etching 33 and fluorescently based ice-plane affinity (FIPA) 28 if IBPs are tagged with fluorescent proteins or dyes.…”
Section: Ibp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, these are used to measure the effectiveness of IBP analogues. Quantitative assays and image analysis routines have been developed to accurately measure thermal hysteresis (TH) activity, 63 66 ice recrystallization inhibition (IRI) activity, 56 , 67 , 68 dynamic ice-shaping (DIS), 69 and ice nucleation (IN) activity. 70 Furthermore, ice-binding can be detected directly, albeit in a qualitative fashion, by ice-etching 33 and fluorescently based ice-plane affinity (FIPA) 28 if IBPs are tagged with fluorescent proteins or dyes.…”
Section: Ibp Activitymentioning
confidence: 99%
“…Ice recrystallization inhibition (IRI) activity is determined by polarized optical microscopy (POM) in a so-called ‘splat-assay’ 89 or ‘sandwich assay’, 67 which probe the rate and extent of ice recrystallization in thin wafers of ice. Splat assays are typically performed in the presence of >2 mM NaCl 90 or 1–100 mM phosphate-buffered saline (PBS) buffer 68 and sandwich assays in the presence of 18–45% sucrose. 56 , 91 In a splat assay quantification of efficacy is based on measurements of the (time-evolution of the) mean (largest) grain size (M(L)GS).…”
Section: Ibp Activitymentioning
confidence: 99%
“…9,84 To quantitatively compare the IRI activity of ice-binding compounds, automated image analysis routines have been developed to monitor the time-evolution of the mean ice grain size, r, and mean largest grain size. 80,86,87 The Koop laboratory demonstrated that r 3 increases linearly with time in 45 wt. % sucrose solutions as predicted by Lifshitz-SlyosovWagner (LSW) theory [ Fig.…”
Section: B Iri Activitymentioning
confidence: 99%
“…71 Monte Carlo simulations on entire 3D ice crystals in the presence of TmAFP and wfAFP-I are also in line with this theory of antifreeze activity since ordered step growth appears inhibited. 91 The prevailing adsorption-inhibition model has been extended and revisited by various groups to account for nonstepwise growth on rough prism planes 86,103,104 and dynamic exchange between adsorbed and free AFPs in a two-step mechanism. 105 Knight et al pointed out that IBPs block normal growth preventing layer growth instead of lateral growth impeding step passage (Fig.…”
Section: A Adsorption-inhibition Modelmentioning
confidence: 99%
See 1 more Smart Citation